2008
DOI: 10.1074/jbc.m705666200
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factor of Potato Virus Y, Genome-attached Terminal Protein VPg, Is a Highly Disordered Protein

Abstract: Potato virus Y (PVY) is a common potyvirus of agricultural importance, belonging to the picornavirus superfamily of RNA plus-stranded viruses. A covalently linked virus-encoded protein VPg required for virus infectivity is situated at the 5 end of potyvirus RNA. VPg seems to be involved in multiple interactions, both with other viral products and host proteins. VPgs of potyviruses have no known homologs, and there is no atomic structure available. To understand the molecular basis of VPg multifunctionality, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 56 publications
5
51
1
Order By: Relevance
“…For Potato virus A (PVA), Potato virus Y, Lettuce mosaic virus, SeMV and RYMV an unfolded/disordered structure of VPg has been described previously (Grzela et al, 2008;Hébrard et al, 2009;Rantalainen et al, 2008;Satheshkumar et al, 2005). VPg proteins lack a unique 3D-structure and exist as a dynamic ensemble of conformations.…”
Section: Introductionmentioning
confidence: 99%
“…For Potato virus A (PVA), Potato virus Y, Lettuce mosaic virus, SeMV and RYMV an unfolded/disordered structure of VPg has been described previously (Grzela et al, 2008;Hébrard et al, 2009;Rantalainen et al, 2008;Satheshkumar et al, 2005). VPg proteins lack a unique 3D-structure and exist as a dynamic ensemble of conformations.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of this Tyr residue with other amino acids abolishes infectivity of both viruses (Murphy et al, 1996;Germundsson et al, 2007). The intrinsically disordered structure of VPg (Grzela et al, 2008;Rantalainen et al, 2008) provides flexibility for many types of interactions with viral and host proteins (Hong et al, 1995;Li et al, 1997;Wittmann et al, 1997;Schaad et al, 2000;Guo et al, 2001;Dunoyer et al, 2004;Lé onard et al, 2004;Thivierge et al, 2008). Interactions between eIF4E or eIF(iso)4E (Wittmann et al, 1997;Schaad et al, 2000;Robaglia and Caranta, 2006) and VPg or NIa are important for virus infectivity (Lé onard et al, 2000;Robaglia and Caranta, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies have shown the intrinsic structural disorder of these proteins. The resulting structural flexibility has been proposed to enable VPg to carry out the variety of functions (16,20,40,44). The N terminus, NTP-binding region, and a short segment in the middle of the protein were speculated to be part of a natively unstructured stretch of amino acids, which may allow these regions to be multifunctional and structurally flexible and thereby facilitate participation of VPg in various interactions.…”
mentioning
confidence: 99%
“…It is argued by Tokuriki et al that viral proteins have a lot of flexibility and a high level of disorder and that they apparently are rapidly evolving proteins, stabilized only in the presence of partners. Accordingly, structural disorder together with polyprotein intermediates and various posttranslational modifications of VPg (18) as well as formation of VPg dimers (16,31,40) give rise to a great variety of functions and complex targets for structure-function studies.…”
mentioning
confidence: 99%